2011
DOI: 10.1007/s00167-011-1794-4
|View full text |Cite
|
Sign up to set email alerts
|

The MRI findings of meniscal root tear of the medial meniscus: emphasis on coronal, sagittal and axial images

Abstract: Diagnostic study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 21 publications
0
111
0
Order By: Relevance
“…A posterior root tear of the MM often causes a severe medial extrusion (>3 mm) of the MM on coronal MR images . However, the amount of LME is usually less than that of the MM extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…A posterior root tear of the MM often causes a severe medial extrusion (>3 mm) of the MM on coronal MR images . However, the amount of LME is usually less than that of the MM extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…They stated that posterior root is difficult to assess by MRI and prone to diagnostic errors because images seemingly show even a single tear as bundles of multiple tears. However, recent reports contributed to raising awareness and interest in the application of MRI for the diagnosis of MMPRTs27,28,29,30,31). Lee et al31) proposed that the MMPRT would not be difficult to diagnose if the diagnosis is based on three different discriminatory features on MRI-plane images along with clinical symptoms: the ghost sign from the sagittal plane (detection rate of 100%), the vertical linear defect (signs of truncation) on the coronal plane (100%), and the radial linear defect on the axial plane (94%) (Fig.…”
Section: Diagnosis Of Mmprtmentioning
confidence: 99%
“…2). Similarly, Choi et al29) suggested that the sensitivity and specificity of MRI diagnosis of MMPRTs could be high if the diagnosis is based on the presence of radial tears on the axial plane, signs of truncation and extrusion on the coronal plane, and the ghost sign from the sagittal plane. Especially, they reported MRI exhibited a 100% positive value for the diagnosis of radial tears on the axial plane.…”
Section: Diagnosis Of Mmprtmentioning
confidence: 99%
“…A root tear could be demonstrated on pre-operative M.R.I in only 72.9% of the patient, while the rest demonstrated degeneration and/or fluid accumulation at the posterior horn without a visible meniscal tear [20]. Other, have reported significantly improved detection ability up to 93.3% sensitivity, 100% specificity and 100% positive predictive value using a variety of magnetic resonance sequences and interpretation signs suggestive of root tears [21] [22] [23]. The detailed for Meniscus tear and its management has been discussed in Figure 1 with a flowchart.…”
Section: Imagingmentioning
confidence: 96%